(untitled) (Foro de Educacion, 2011)
The actual concept of pedagogy in China is understood as an interdimensional construct which objetive is to facilitate the educational practice. In order to reach this goal, the education sciences have taken information from different fields of sciences, both Chinese and from foreign countries. However, the evolution of this concept has undergone numerous modifications until the actual concept was approved for teachers and researchers. To understand its current meaning, as a first step established as a discipline, but also in constant evolution, is needed to cover every social issues, which are in constant changing. The aim of this article is to present the most important historical facts, which helped to reach the application of the actual concept. Both, educational and researching methods that exists today in China, has been a challenge because of the political, the ideological and the academic situation.